Rancang Bangun Sistem Kendali dan Pemantauan Ketinggian Air Pada Panci Penguapan Terbuka Berbasis Website - Dolf, Fredericus Dandani; Wigyarianto, F. Trias Pontia; Priyatman, Hendro (JiTEKH, 2024)
During the dry season, the water evaporation process experiences a significant increase resulting in a rapid decrease in water volume. Conversely, during the rainy season, the open evaporation pan can quickly fill up with rainwater, often causing overflow that disrupts the evaporation measurement process, thus requiring manual intervention to drain or refill the evaporation pan. One proposed solution to address this issue is by implementing an automatic water control system, water temperature monitoring, and water level measurement. The system design consists of two main aspects, namely hardware and software design. Hardware design involves creating a system block diagram and electronic circuit schematic diagrams. Meanwhile, software design includes program and WEB interface design. This research method involves the use of JSN-SR04T ultrasonic sensor, DS18B20 temperature sensor along with ESP32 DevKitC V4 device. Based on the test results, the ultrasonic sensor showed the highest error value of 19.38% with an average error percentage of 4.62% from 55 test runs. Meanwhile, the highest error value on the temperature sensor reached 3.46%, with an average error percentage of 1.46%. Sensor readings, pump status, and solenoid valve status are displayed in real-time on an LCD and Thinger.io dashboard.